ABCG subfamily (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
This family of 'half-transporters' act as homo- or heterodimers; particularly ABCG5 and ABCG8 are thought to be obligate heterodimers. The ABCG5/ABCG heterodimer sterol transporter structure has been determined [4], suggesting an extensive intracellular nucleotide binding domain linked to the transmembrane domains by a fold in the primary sequence. The functional ABCG2 transporter appears to be a homodimer with structural similarities to the ABCG5/ABCG8 heterodimer [7].